WEDGE-SHAPED SUBRETINAL HYPOREFLECTIVITY IN GEOGRAPHIC ATROPHY. Issue 9 (September 2015) - Querques, Giuseppe; Capuano, Vittorio; Frascio, Pietro; Zweifel, Sandrine; Georges, Anouk; Souied, Eric H.
Abstract : Purpose: To describe wedge-shaped subretinal hyporeflectivity, a peculiar spectral domain optical coherence tomography finding in geographic atrophy (GA) areas of atrophic age-related macular degeneration. Methods: We reviewed the charts of consecutive patients with GA who presented between January 2012 and December 2013. A standardized imaging protocol was performed in all patients, which included blue fundus autofluorescence, and spectral domain optical coherence tomography. Results: Wedge-shaped subretinal hyporeflective lesions were found in 12 of 161 included eyes (11 of 94 consecutive patients, 6 males/5 females, mean age 79.6 ± 9.3 years). On spectral domain optical coherence tomography, regions immediately adjacent to the wedge-shaped subretinal hyporeflective lesions were characterized by absence of the hyporeflective outer nuclear layer, the hyperreflective external limiting membrane, the ellipsoid zone, the interdigitation zone, and the retinal pigment epithelium. On "en face" images, they appeared as round-oval hyporeflectivities delimited by hyperreflective borders, which we interpreted as the outer plexiform layer. Mean GA area was significantly larger in eyes with as compared with eyes without wedge-shaped subretinal hyporeflective lesions. Overall, the dimensions of the wedge-shaped subretinal hyporeflective lesions did not change after a mean of ∼15 months. Conclusion: Wedge-shaped subretinal hyporeflectivity, a previously unreported peculiar finding in GA areas of atrophic age-related macular degeneration eyes, appears delimited internally by the hyperreflective outer plexiform layer and externally by the hyperreflective Bruch membrane. These lesions, which are detected in eyes with large GA (even though stable over time), should be recognized and distinguished from subretinal fluid (and other exudative signs of age-related macular degeneration) because their presence should not require prompt treatment. Abstract : Wedge-shaped subretinal hyporeflectivity, a previously unreported peculiar finding in geographic atrophy areas of atrophic age-related macular degeneration eyes, appears delimited internally by the hyperreflective outer plexiform layer and externally by the hyperreflective Bruch membrane.